2018
DOI: 10.1136/openhrt-2018-000860
|View full text |Cite
|
Sign up to set email alerts
|

Web-based cardiacREhabilitatioNalternative for those declining or dropping out of conventional rehabilitation: results of the WREN feasibility randomised controlled trial

Abstract: IntroductionCardiac rehabilitation (CR) is typically delivered in hospital-based classes and is recommended to help people reduce their risk of further cardiac events. However, many eligible people are not completing the programme. This study aimed to assess the feasibility of delivering a web-based CR intervention for those who decline/drop out from usual CR.InterventionA web-based CR programme for 6 months, facilitated with remote support.MethodsTwo-centre, randomised controlled feasibility trial. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
0
12
0
2
Order By: Relevance
“…However, the mean HADS anxiety scores were significantly higher in more depressive patients compared to the lower level depression group patients with comorbid depression (− 5.17 — 95% CI -5.47 to − 4.87). This difference is relatively high given that HADS is scored out of 21 and this has not been seen in the most recent CR randomised controlled trial REACH HF and a feasibility randomised controlled trial WREN [ 38 , 39 ]. In contrast to other studies, this paper investigated comorbid anxiety, which was prevalent in 52.4% of participants with higher level depressive symptoms, and this association was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mean HADS anxiety scores were significantly higher in more depressive patients compared to the lower level depression group patients with comorbid depression (− 5.17 — 95% CI -5.47 to − 4.87). This difference is relatively high given that HADS is scored out of 21 and this has not been seen in the most recent CR randomised controlled trial REACH HF and a feasibility randomised controlled trial WREN [ 38 , 39 ]. In contrast to other studies, this paper investigated comorbid anxiety, which was prevalent in 52.4% of participants with higher level depressive symptoms, and this association was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…This was successfully tested in patients who turned down face-to-face rehabilitation. 48 A systematic review concluded that home-based interventions attained similar outcomes to centrebased models. 49 Of note, broader NHS initiatives to more widely utilise digital healthcare interventions and telemedicine recognise growing internet utilisation and confidence among older patients.…”
Section: Mode Of Deliverymentioning
confidence: 99%
“…Data demonstrated that users' exercise capacity and HR-QoL improved after completing the programme (22).…”
Section: New Models Of Rehabilitationmentioning
confidence: 98%
“…As an example, “Activate Your Heart” is a well-established digital cardiac rehabilitation programme and was evaluated in several different locations. Data demonstrated that users' exercise capacity and HR-QoL improved after completing the programme ( 22 ).…”
Section: Introductionmentioning
confidence: 99%